2006
DOI: 10.1002/anie.200603128
|View full text |Cite
|
Sign up to set email alerts
|

Selective Platination of Modified Oligonucleotides and Duplex Cross‐Links

Abstract: Since synthetic oligonucleotides complementary to mRNA sequences were shown to inhibit Rous sarcoma virus replication, [1] oligonucleotide chemists have synthesized all types of analogues to render oligonucleotides suitable as antisense agents. In this context, platinated oligonucleotides have been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Ligand exchange by transition metals provides an alternative basis for bipedal diffusion along DNA but few examples have yet been published. To date, Pt(II) migration has only been observed over a single bipedal transfer 54,62,63 . A related system utilizing Pd(II) with a track of pyridine ligands alternatively required addition of heat and a pH change to drive bipedal walking 64 .…”
Section: Resultsmentioning
confidence: 99%
“…Ligand exchange by transition metals provides an alternative basis for bipedal diffusion along DNA but few examples have yet been published. To date, Pt(II) migration has only been observed over a single bipedal transfer 54,62,63 . A related system utilizing Pd(II) with a track of pyridine ligands alternatively required addition of heat and a pH change to drive bipedal walking 64 .…”
Section: Resultsmentioning
confidence: 99%
“…In studies aimed at understanding how transplatin distorts nucleic acid structure differently than its cis counterpart, it was discovered that pre-formed 1,3 G*pNpG* transplatin-derived adducts on DNA readily rearrange into intermolecular cross-links when annealed to complementary oligonucleotides [88][89][90]. Subsequent mechanistic studies have shown that isomerization reactions between these 1,3 G*pNpG* transplatin adducts and complementary oligonucleotides are sequence-specific [91], can result in unusual G-N7* to C-N3* crosslinks [89], and are also observed using 2'-OMe [92] and chemically modified RNAs [93]. Further work has shown that transplatin-modified 2'-OMe RNAs [94] and cisplatinmodified RNAs [95,96] can be used as antisense oligos for attenuating gene expression in cell lysates and in living cells.…”
Section: Transplatin Cross-linking and Pt(ii) Drug Conjugatesmentioning
confidence: 99%
“…Subsequent mechanistic studies have shown that isomerization reactions between these 1,3 G*pNpG* transplatin adducts and complementary oligonucleotides are sequence-specific [91], can result in unusual G-N7* to C-N3* cross-links [89], and are also observed using 2’-OMe [92] and chemically modified RNAs [93]. Further work has shown that transplatin-modified 2’-OMe RNAs [94] and cisplatin-modified RNAs [95,96] can be used as antisense oligos for attenuating gene expression in cell lysates and in living cells.…”
Section: In Vitro Studies Of Rna-pt(ii) Adductsmentioning
confidence: 99%